If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2m + 3p + 4m + -2p = 0 Reorder the terms: 2m + 4m + 3p + -2p = 0 Combine like terms: 2m + 4m = 6m 6m + 3p + -2p = 0 Combine like terms: 3p + -2p = 1p 6m + 1p = 0 Solving 6m + 1p = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1p' to each side of the equation. 6m + 1p + -1p = 0 + -1p Combine like terms: 1p + -1p = 0 6m + 0 = 0 + -1p 6m = 0 + -1p Remove the zero: 6m = -1p Divide each side by '6'. m = -0.1666666667p Simplifying m = -0.1666666667p
| [-x^2]+4x-6=0 | | 2/3z-6=12 | | 34-4=8 | | Q=5(x+p) | | -0.2x^2-0.6x+1.5=0 | | 2=g-11 | | 7(2n+5)=9(8n+8)+7 | | 0=95+7.50t-4.9t^2 | | 67=5x+2(4x-12) | | 4x-7x+5=-5x+4x+11 | | 6(t+7)=-4t+12 | | 8x^3+6y^3= | | 4(-7)=4x+28 | | -22=x+12 | | 2b+9=b+11 | | 2/3r-6=12 | | 11.5(2p+1.50)=11.50 | | [x^2]-12x+36=0 | | -0.2x^2+0.6x-1.5=0 | | 2a+3y=9 | | 84=4x+4(2x-3) | | 7x+4=4x^2 | | 3-a=3a+7 | | -6(-8n-4)=24-7n | | 8(3a-5)4(2a+3)=12 | | 5x+6x-4=7 | | 5y+2(y-8)=4(y-1)-3 | | (2x+9)-(4x+7)-6x=76 | | 156=6x+3(5x-18) | | 7x+146+x+48+65=147 | | 3-a=2a+7 | | 5z-3y+2x=5 |